2012
DOI: 10.1177/1049732312458370
|View full text |Cite
|
Sign up to set email alerts
|

Improving Client-Centered Brain Injury Rehabilitation Through Research-Based Theater

Abstract: Traumatic brain injury often results in physical, behavioral, and cognitive impairments perceived by health care practitioners to limit or exclude clients' full participation in treatment decision making. We used qualitative methods to evaluate the short-and long-term impact of "After the Crash: A Play About Brain Injury", a research-based drama designed to teach client-centered care principles to brain injury rehabilitation staff. We conducted interviews and observations with staff of two inpatient neurorehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 104 publications
0
43
0
1
Order By: Relevance
“…Research-informed productions have been developed for the purpose of disseminating research findings to healthcare providers, students, patients and the general public on the topics of mental illness,34 41 substance use,42 breast cancer,43 ovarian cancer,44 end of life care,45 46 traumatic brain injury47 48 and Alzheimer's disease,49–51 among others 29. Indeed, of the 71 studies reviewed by Boydell et al , after photo-based methods (n=23), theatre was the most common arts-based KTE method used by health researchers (n=21) 40.…”
Section: Discussionmentioning
confidence: 99%
“…Research-informed productions have been developed for the purpose of disseminating research findings to healthcare providers, students, patients and the general public on the topics of mental illness,34 41 substance use,42 breast cancer,43 ovarian cancer,44 end of life care,45 46 traumatic brain injury47 48 and Alzheimer's disease,49–51 among others 29. Indeed, of the 71 studies reviewed by Boydell et al , after photo-based methods (n=23), theatre was the most common arts-based KTE method used by health researchers (n=21) 40.…”
Section: Discussionmentioning
confidence: 99%
“…Identified themes did not include practices impacted by the intervention (see Kontos et al . , for intervention evaluation).…”
Section: The Studymentioning
confidence: 99%
“…It is possible this is similar to the high levels of "self-monitoring" engaged in by US nurses who, in the context of managed care, opted for disengagement since resources to support emotion work were scant (Bone, 2002, p.146). In Canada, the enormity of clients' unmet rehabilitative and psychiatric needs under inadequately publicly funded rehabilitative care (Kontos et al, Forthcoming;Kontos et al, 2012) may render staff unable to incorporate grief-related emotion work given existing demands of practice. It is also possible that practitioners' suppression of empathy is, as other studies have shown, a consequence of individual-level behaviours such as compassion fatigue (Robins, Meltzer, & Zelikovsky, 2009), discipline specific training (Papadimitriou, 2008), or institutional policy directives (Kontos et al, Forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…Theatre contributes significantly to medical education because it has "a uniquely compelling emotional quality, making it difficult to avoid or intellectualize the struggles and suffering portrayed" (Shapiro & Hunt, 2003, p. 923). While there is increasing empirical support for the effectiveness of research-based drama for learning about illness and humane patient care in various clinical areas (Gray et al, 2003;Gray et al, 2000;Shapiro & Hunt, 2003), it is used with surprising infrequency in educational interventions to improve the quality of brain injury rehabilitation (for exceptions see Colantonio et al, 2008 andKontos et al, 2012).…”
Section: Research-based Theatrementioning
confidence: 99%
See 1 more Smart Citation